Diagnosis of subarray‐structured base station antennas in a compact setup based on solving linear equations - Li, Mengting; Zhang, Fengchun; Fan, Wei (IET microwaves, antennas & propagation, 2023)
Since the total number of the antenna elements can be up to hundreds in a massive multiple‐input multiple‐output (MIMO) system, subarray‐structured base station (BS) array configurations are widely adopted to achieve a good cell coverage and to reduce the required number of radio frequency chains at the same time. It is crucial for any BS product to ensure that the antenna elements perform correctly as expected. Therefore, the necessity of array diagnosis is evident, especially for large BS arrays. Furthermore, it is essential that the diagnosis can be achieved in a compact and cost‐effective setup with high measurement efficiency (i.e. only a few measurement samples are required). The principle of the diagnosis method presented in this article is to obtain the S‐parameters between the subarrays and the probe via solving linear equations. In the simulation, a BS array composed of 16 subarrays with each containing 3 elements is used to validate the diagnosis method at 3.5 GHz. An array composed of 4 subarrays with each containing 3 elements was used in the measurements to verify the diagnosis method with two different phase tuning matrices at 3 GHz. Successful diagnosis results have been achieved in both the simulations and the measurements.